MRI evaluation of the effects of extension exercises on the disc fluid content and location of the centroid of the fluid distribution. (February 2018) - Abdollah, Vahid; Parent, Eric C.; Battié, Michele C.
Abstract: Background: McKenzie prone press-up exercises have been hypothesised to reduce intradiscal pressure, allowing fluid to be reabsorbed into the disc, which could improve the internal stability and local chemical milieu of the disc, potentially reducing symptoms. Objective: To investigate the immediate effects of prone press-up exercises on lumbar disc fluid content and movement. Design: Quantification of MRI changes before and after a single exercise session. Methods: The mid-sagittal T2 -weighted MR images of 22 volunteers with low back pain were obtained before and immediately after performing press-up exercises. The whole disc and nucleus regions of the L4-5 and L5-S1 discs were then segmented, and their mean signal intensity (MSI) and signal intensity weighted centroid (SIWC) were computed to estimate disc fluid content and displacement. Results: There were no significant differences between the MSI and the vertical position of the SIWC of the whole disc before and after extension at either disc level (effect size [ES]: −0.23 to 0.09). There was a significant anterior displacement (0.1 ± 5.4 mm) of the location of the SIWC of the disc after extension exercise at L4-5 (ES: 0.22), but not at L5-S1 (ES: 0.00) or at either level for the nucleus region (ES: −0.06; 0.16). Conclusion: Little evidence was found supporting the hypothesis that press-up exercises affect disc fluid content and distribution. Novel parameters reflecting fluid distribution detected similar or larger effects of the extension than MSI. If such exercises are effective in reducing symptoms, it is likely through other mechanisms than by changing fluid content or distribution. Graphical abstract: Highlights: The signal intensity weighted centroid (SIWC) is a novel reliable non-invasive method for quantifying the effects of loading. Except for a more anterior SIWC in the L4L5 disc after extension, there were no significant SIWC differences. No significant differences were found in disc or nucleus mean signal intensity after extension exercise at L4L5 and L5S1. Prone press-up extension did not increase disc fluid content, but may anterior fluid redistribution at lower lumbar levels.